Adverse Childhood Experiences: A 20‐Year Content Analysis of American Counseling Association and American School Counselor Association Journals. (13th September 2020) - Zyromski, Brett; Baker, Emily; Betters‐Bubon, Jennifer; Dollarhide, Colette T.; Antonides, Joseph
Abstract : The purpose of this content analysis was to illustrate trends related to the use of the term adverse childhood experiences (ACEs), or terms related to the 10 components of ACEs, within 140 peer‐reviewed articles published in 22 journals affiliated with the American Counseling Association (ACA) and the American School Counselor Association (ASCA) between 1998 and 2018. Of the 9, 120 articles published in the 22 ACA‐ and ASCA‐affiliated journals in that time, only three articles (0.03%) explicitly mentioned the term adverse childhood experiences in the title, abstract, or keywords. Authors of 93 journal articles mentioned terms related to the original 10 categories of ACEs 104 times (1.0% of all published articles). The need for consistent language across research and practice is highlighted. Implications include ways that the counseling field may benefit from an increased clarity and focus around ACEs.